The Zero Trimester : Pre-Pregnancy Care and the Politics of Reproductive Risk - Waggoner, Miranda R. (Book collections on Project MUSE., 2017)
"A healthy pregnancy is now defined well before pregnancy even begins. Public health messages promote pre-pregnancy health and health care by encouraging reproductive-age women to think of themselves as mothers before they think of themselves as women. This happens despite little evidence that such an approach improves maternal and child health. This book examines the dramatic shift in ideas about reproductive risk and birth outcomes over the last several decades, unearthing how these ideas intersect with the politics of women's health and motherhood at the beginning of the twenty-first century."--Provided by publisher.